(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The supercapacitor is a booming technology whose popularity is increasing as the number of electric vehicles are increasing. The supercapacitor is a technology which will be a supporting pillar for electric vehicles and hydrogen vehicles to take the market. Supercapacitors will reduce stress on the main energy storage device thereby increasing their life and bettering performance. In the supercapacitor electrode, electrolyte and separators are the main parts. The effect of electrode, electrolytes, and separators have been extensively studiedseparately in the past, but their combined effect has not been studied. Each of the three parts has one important parameter which contributes the maximum in capacitance of supercapacitor. These parameters are taken into consideration and their individual and interaction effect on capacitance of supercapacitor is being studied in this paper. A statistical model has been used for analysis. The generated statistical model has been validated at a few points and error is within 5%. This statistical model can be utilized by researchers and manufacturers in due course.